A comparison of 141 polymacon (Iogel) and 140 poly(methyl methacrylate) intraocular lens implants. Issue 2 (February 1992) - Lowe, K J; Easty, D L
Abstract : In a prospective controlled trial 290 consecutive patients were randomly allocated a polymacon or a poly(methyl methacrylate) (PMMA) intraocular lens. Early Treatment of Diabetic Retinopathy Study (ETDRS) acuity charts gave similar results with both lenses. However Pelli-Robson contrast sensitivity charts gave a better result with PMMA lenses. Polymacon lenses appeared to remain free of any adhesions after implantation raising the question of long term stability. Four patients experienced problems related to this, three involved total lens dislocation. Seven patients developed early 'fibrin' membranes coating the polymacon lens, of which three were florid.